Shock-driven amorphization and melting in Fe2⁢O3 - Crepisson, C; Amouretti, A; Harmand, M; Sanloup, C; Heighway, P; Azadi, S; McGonegle, D; Campbell, T; Pintor, J; Chin, DA; Smith, E; Hansen, L; et al. (American Physical Society, 2025)
We present measurements on Fe2O3 amorphization and melt under laser-driven shock compression up to 209(10) GPa via time-resolved in situ x-ray diffraction. At 122(3) GPa, a diffuse signal is observed indicating the presence of a noncrystalline phase. Structure factors have been extracted up to 182(6) GPa showing the presence of two well-defined peaks. A rapid change in the intensity ratio of the two peaks is identified between 145(12) and 151(12) GPa, indicative of a phase change. The noncrystalline diffuse scattering is consistent with shock amorphization of Fe2O3 between 122(3) and 145(12) GPa, followed by an amorphous-to-liquid transition above 151(12) GPa. Upon release, a noncrystalline phase is observed alongside crystalline α-Fe2O3. The extracted structure factor and pair distribution function of this release phase resemble those reported for Fe2O3 melt at ambient pressure.